Linguistic Features of Texts and Psychological Characteristics of Speech Activity Products of Students with Different Signaling Systems Domination - Fomina, Natalya; Mirchetich, Marina (East European Journal of Psycholinguistics, 2014)
The paper presents complex research results of texts as products of individual speech activity of students with different signaling system domination, in particular their linguistic, speech, substantial-semantic features and motivational, emotional, regulative, cognitive, dynamic characteristics of authors. the results of the study have shown that the students with the first signaling system domination tended to be more emotional, dynamic, communication and speech-oriented, despite many grammar errors and large text size. By contrast, the students with the second signaling system domination tended to be less emotional, dynamic and less imaginative, but more . Their texts contained a number of abstract words, non-relevant repetitions, complex sentences with causal and conditional subordinate clauses. References Kadyrov, B. R. (1990). Sposobnosti i Sklonnosti [Abilities and Tendencies: A Psychophysiological Research]. Tashkent: Fun. Fomina, N. A. (2002). Svoistva Lichnosti i Osobennosti Rechevoi Deyatelnosti [Personality Features and Speech Activity Peculiarities]. Ryazan: Uzorochye. Fomina, N. A. (2011). Kompeksnoye izucheniye proyavleniy lichnosti v rechevoy deyatelnosti [A compex study of personality manifestation in speech activity]. Psychological Prospects, 18, 257–270. Fomina, N. A., Mirchetich, M. A. (2013). Lingvisticheskiye i psikhologicheskiye kharakteristiki produktov rechevoy deyatelnosti studentov s preobladaniem pervoy signalnoy sistemy [Linguistic and psychological characteristics of speech activity products of students with the first signaling system domination]. Psykholingvistyka, 14, 152−163. Fomina, N. A., Mirchetich, M. A. (2014). Lingvisticheskiye kharakteristiki tekstov i psikhologicheskiye osobennosti rechevykh deystviy studentov s preobladaniem vtoroy signalnoy sistemy [Linguistic features of texts and psychological characteristics of speech activity products of students with the second signaling system domination] Vestnik RUDN. Series Psychology and Pedagogy, 1, 60−67.